Simbol-Simbol Agama - M. Husein A. Wahab (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2011)
The symbol is a sacred sign in the religious life. The symbols consist of various systems, models and forms that relate to the human‟s need of religion. The Symbol systems are the accumulation of the religious based on knowledge, ethic, moral, art and faith that are implemented in various rituals and worship. All of these model systems are formed in various patterns in accordance with the religious demands of human needs and religious homo simbolicus.